FORMAÇÃO CONTINUADA E OS SABERES EXPERIENCIAIS DE PROFESSORES DAS ESCOLAS MUNICIPAIS DE SÃO LUÍS: implicações teórico-práticas - Branco, Ana Cássia Castelo (2008)
Reflexion on the questions related to the formation of the teachers and some of their specificities as perspective of this paper. The text is resulting from a field research about the continued Formation and the Experiencial Knowledges of teachers at a Unit of Municipality Basic Education in São Luís and their implications theoretical-practical. It deals with a case study, so at the sphere of this paper which is prone to study the repercussion of the mentioned formative, process developed at the school s rooms as to the docent s practice. The investigative course based itself in the legal aspects linked to the education and the theoretical contributions from exponentials like Althusser (1999), Bourdieu (1983), Gramsci (1991), Forquím (1995) and others. Its focus is centered upon the teachers, school managers and pedagogical coordinator who get their functions at the Fundamental teaching and considered that all of them take part at the activities linked to the São Luís te Quero lendo e Escrevendo Programme, developed by the Municipal Secretary of Education SEMED, which has as one of its segments the teacher , continued formation. Besides the documental analysis, the bibliographical inquire, it was applied the questionnaire and it was developed a half - structured interview as well as the observation, aiming the recollection of informations. From the interpretations upon the talking of the school representatives, studying field, it was contemplated aspects linked to the occurrence of the continued formation, at the school and its importance to the teachers.